THE IMPACT OF HUMAN RESOURCE AGILITY ON KNOWLEDGE SHARING BEHAVIORS - ANALYTICAL RESEARCH AT THE UNIVERSITY OF ANBAR - Omar qais Jameel; Dr. Hussam Ali Mhaibes (Scholar Express Journals, 2022)
The research aims to test the effect of human resource agility as an explanatory variable on the behavior of knowledge sharing as a responding variable, at the University of Anbar, and the descriptive analytical approach was adopted in the completion of this research, and the research community included all faculty members, and data was collected from (276) respondents representing the research sample, which is b (Dean, Associate Dean, Head of Department, Department Rapporteur, Division Officer, Unit Officer, Teaching), a stratified proportional random sample in all the formations of the University of Anbar, based on a questionnaire that included (42) items, through a set of appropriate statistical methods ( The arithmetic mean, standard deviation, coefficient of variation, relative importance, Pearson correlation coefficient, and multiple linear regression coefficient). The results showed the validity of the hypotheses about the existence of an effect of human resource agility in cognitive sharing behavior, which indicates the active role of human resource agility in influencing sharing behavior. Knowledge at the University of Anbar
Keywords: Human resource agility; knowledge sharing behavior; University of Anbar